Impact of body composition on pathological response to neoadjuvant immunotherapy in dMMR/MSI-H colorectal cancer - Zeng, Ziyang; Zhou, Jian; Zhang, Weili; Peng, Jianhong; Li, Yuan; Jin-si-han, E-er-man-bie-ke; Wang, Hao; Lian, Shaopu; Feng, Cheng; Xie, Chuanmiao; Pan, Zhizhong; Lu, Zhenhai (Frontiers in Immunology, 2025)
BackgroundObesity and overweight have been suggested as a potential predictor of favorable outcomes in certain malignancies treated with immunotherapy. However, most studies have relied on BMI as a proxy for adiposity, without fully considering the distinct roles of fat and lean tissues. This study aimed to explore the association between body composition and treatment response in colorectal cancer patients receiving neoadjuvant PD-1 inhibitor therapy.MethodsPatients with dMMR/MSI-H colorectal cancer undergoing neoadjuvant PD-1 blockade were included in this study. Body composition parameters were measured using baseline CT images. Pathological response was assessed using tumor regression grade (TRG). Univariate and multivariate analyses were performed to examine the association between body composition variables (total adipose tissue, visceral adipose tissue, subcutaneous adipose tissue, visceral-to-subcutaneous adipose tissue ratio, and skeletal muscle) and pathological complete response (pCR) rates. Correlation analysis was conducted to detect the relationship between body composition and lipid profiles.ResultsA total of 84 patients were included in the analysis. Patients with poor treatment response exhibited significantly lower levels of visceral adipose tissue (VAT), total adipose tissue (TAT), and BMI. On multivariate analysis, higher VAT volume and elevated circulating lymphocyte count were independently associated with increased pCR rates. The positive association between VAT and treatment response was consistent across most subgroups except in patients aged ≥ 65, where the effect tended to be reversed. Additionally, VAT volume correlated positively with triglycerides and negatively with high-density lipoprotein cholesterol.ConclusionHigher visceral adipose tissue volume is associated with improved pathological complete response in dMMR/MSI-H colorectal cancer patients treated with PD-1 inhibitors. However, this favorable effect of visceral adiposity may be diminished or reversed in elderly patients (≥ 65 y), highlighting the potential influence of aging on the metabolic-immune interplay in immunotherapy response.